A velhice, suas perdas e ganhos: História de vida contada sob o prisma da salutogenêse - (:unkn) unknown (FEFF - Faculdade de Educação Física e Fisioterapia, 2025)
The life history (HV) methodology is an important factor in the study of aging, as it allows a detailed understanding of the trajectory of each individual. This method offers an in-depth analysis of the experiences and challenges faced throughout life, and is essential for understanding aging in different contexts. In this work, we present the story of Mr. Antenor, who, since childhood, lived in the rural area, experiencing aging within the rural context, characterized by hard work in the field. Objective: The aim of this study is to analyze how resilience resources are created in the aging process. . Method: The methodology of life history, based on the salutogenic theory, was adopted to analyze Antenor's trajectory. The story was collected in the context of the "AM 80+" study in Manaus, through interviews conducted in 2023. The approach used was open and unstructured, focusing on stressors, health resources, and body practices. The interview was recorded, transcribed and validated by the participant. The analysis followed a process of coding and grouping of themes, based on guiding concepts. Results: The interview provided a detailed analysis of Antenor's life history, highlighting the stressors and resources he used to face difficulties throughout his life. The focus was to understand how he overcame each challenge, without allowing stressors to dominate his trajectory.
Keywords: História de vida; Life story; Envelhecimento; Salutogênese; CIENCIAS DA SAUDE: FISIOTERAPIA E TERAPIA OCUPACIONAL; .; .